PENGARUH KEMAMPUAN MENYUSUN LAPORAN KEUANGAN, LITERASI KEUANGAN, KEMAMPUAN MANAJERIAL, DAN PENGGUNAAN TEKNOLOGI INFORMASI TERHADAP KINERJA UMKM YANG DIBINA LPNU DI KABUPATEN JEPARA - Yela Sashafilda, Aurelia; Sofwan, Ali (Jurnal Revenue : Jurnal Ilmiah Akuntansi, 2025)
The study aims to examine the effect of the ability to prepare financial reports, financial literacy, managerial ability, and the use of information technology on the performance of MSMEs in Jepara Regency. The population used is MSMEs fostered by LPNU Jepara with a total of 100 MSME players. Saturated sample is the method used to take samples. The use of this method resulted in 100 respondents. The questionnaire was chosen as the technique used in data collection.  The data that has been obtained is analyzed using multiple linear regression analysis assisted by the use of the SPSS application. Referring to the research data that has been processed shows that all independent variables, namely the ability to prepare financial reports, financial literacy, managerial ability, and the use of information technology have a positive and significant influence on the performance of MSMEs. The magnitude of the influence of the ability to prepare financial reports, financial literacy, managerial ability, and the use of information technology affects the performance of MSMEs by 35.6%, while the remaining 64.4% is explained by other variables outside the research that the researchers conducted